(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The objective of the work is to analyze the symbols present in cigarette advertisements in the 70’s, making a quantitative survey of the symbols shown in these advertisements. The use of different strategies is verified, with predominance in the use of imaginary associations, especially associations with heterosexual couples, sophistication in clothing, extreme sports and food.